A novel enterovirus in lambs with poliomyelitis and brain stem encephalitis. Issue 2 (21st December 2021) - Weissenböck, Herbert; Ebinger, Arnt; Gager, Anna Maria; Thaller, Denise; Höper, Dirk; Lichtmannsperger, Katharina; Weissenbacher‐Lang, Christiane; Matt, Julia; Beer, Martin
Abstract: An Austrian organic dairy sheep farm experienced cases of recumbency and sudden deaths in 3‐ to 4‐week‐old lambs. Two animals were subjected to thorough clinical and pathological investigations. Pathohistological analysis identified severe nonsuppurative myelitis and mild nonsuppurative encephalitis. A reverse‐transcription quantitative PCR (RT‐qPCR) assay for the recently discovered ovine picornavirus causing comparable lesions scored negative. By next‐generation sequencing‐based metagenomics, a nearly complete genome of a novel enterovirus could be detected and assembled. In situ hybridization using a specifically designed probe revealed robust signals in affected motoneurons of the spinal cord suggesting a causative role of the novel virus.